Implementation of Minister of Transportation Regulation No. 819 of 2018 by the Harbormaster Office and Port Authority: Challenges, Communication Strategies, and Fishermen’s Reactions in Dumai City, Riau Province - Mulyani, Iwed; Wahyuni, Hermin Indah; Prihatin, Silverius Djuni (TEMALI : Jurnal Pembangunan Sosial, 2024)
The waters of Dumai City, Riau Province, serve as an international transportation route with a strategic position in economic and industrial growth. Minister of Transportation Regulation No. 819 of 2018 was issued to regulate shipping zones and ensure the safety of port service users. However, this regulation has sparked numerous complaints from the public, particularly fishermen, due to livelihood restrictions that directly increase operational costs. To address these negative reactions, the Dumai Port Authority Office (KSOP) plays a significant role by implementing various measures in enforcing Ministerial Regulation No. 819 of 2018. This study aims to understand the communication strategies used by the Dumai Port Authority Office, especially in coordinating with stakeholders. This research uses a qualitative method, gathering data through observation and interviews. The results show that the Dumai Port Authority Office, along with the Class I Dumai Navigation District, PT Kilang Pertamina Internasional, and PT Wilmar Cahaya Asia, has a strategic role with the ability to influence policy direction and implementation. The Dumai Port Authority Office adopts strategies that involve collaboration with strategic partners, annual outreach programs, the distribution of social assistance and life jackets to the fishing community, and cooperation with relevant agencies and government institutions, including the Water Police, to monitor vessels violating regulations. Additionally, KSOP involves the participation of the community and companies, including the certification and standardization of maritime safety instruments. This study contributes to the discussion on the effectiveness of communication strategies in maritime policy implementation, where this approach can enhance understanding and acceptance of regulations within the maritime community.